2017
DOI: 10.1002/hbm.23904
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal tract diffusion properties and robotic visually guided reaching in children with hemiparetic cerebral palsy

Abstract: Perinatal stroke is the leading cause of hemiparetic cerebral palsy (CP), resulting in life-long disability. In this study, we examined the relationship between robotic upper extremity motor impairment and corticospinal tract (CST) diffusion properties. Thirty-three children with unilateral perinatal ischemic stroke (17 arterial, 16 venous) and hemiparesis were recruited from a population-based research cohort. Bilateral CSTs were defined using diffusion tensor imaging (DTI) and four diffusion metrics were qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 90 publications
(131 reference statements)
0
57
1
2
Order By: Relevance
“…Perinatal stroke disrupts typical CST development through neuronal cell loss, axonal degeneration and demyelination processes, all of which lead to motor impairment. Prior DWI studies have demonstrated greater diffusivity in the lesioned CST after perinatal stroke in children with UCP (Hodge et al, ; Kuczynski et al, ; Kuo et al, ; Manning et al, ; Weinstein et al, ). We have confirmed these results for three tensor‐based measures: MD, AD, and RD, which all showed significantly greater diffusivity in the lesioned compared to the nonlesioned CST.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Perinatal stroke disrupts typical CST development through neuronal cell loss, axonal degeneration and demyelination processes, all of which lead to motor impairment. Prior DWI studies have demonstrated greater diffusivity in the lesioned CST after perinatal stroke in children with UCP (Hodge et al, ; Kuczynski et al, ; Kuo et al, ; Manning et al, ; Weinstein et al, ). We have confirmed these results for three tensor‐based measures: MD, AD, and RD, which all showed significantly greater diffusivity in the lesioned compared to the nonlesioned CST.…”
Section: Discussionmentioning
confidence: 98%
“…However, we were unable to draw conclusions about CST microstructural organization across lesion subtypes due to the small sample size (Reid, Pagnozzi, et al, ). Recently, Kuczynski et al, () compared diffusion properties of the lesioned CST between children with arterial and venous infarctions, finding differences in MD, AD, and RD in the arterial but not the venous subgroup as compared to controls. Differentiating lesion phenotype in future DWI analyses may help identify subgroups of children with distinctive patterns of CST microstructural organization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is no universal tractographic approach to delineate the CST due to interference of other crossing fibre tracts (although it may be overcome when the CP or the PLIC stand as a single ROI) [15]. Some authors proposed using the CP and the PLIC as two ROI where all the fibres would run through [1,14]. At our institution we abandoned this technique and now use a custom DTI technique for all our patients because we believe that estimating the CST around the tumours at the eloquent cortex should utilize a variety of ROIs rather than a standardized a set due to several of the reasons indicated before.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing recent methods of DTI of the CST, we utilized two basic type of ROIs to outline the CST [1,[4][5][6]12,14,15]. Two main ROIs were designated as "start points": the cerebral peduncle (CP) and the posterior limb of internal capsule (PLIC).…”
Section: Image Acquisitionmentioning
confidence: 99%